Efforts towards the optimization of a bi-aryl class of potent IRAK4 inhibitors. Issue 17 (1st September 2016) - Hanisak, Jennifer; Seganish, W. Michael; McElroy, William T.; Tang, Haiquin; Zhang, Rui; Tsui, Hon-Chung; Fischmann, Theirry; Tulshian, Deen; Tata, James; Sondey, Christopher; Devito, Kristine; Fossetta, James; et al.
Graphical abstract: Abstract: IRAK4 has been identified as potential therapeutic target for inflammatory and autoimmune diseases. Herein we report the identification and initial SAR studies of a new class of pyrazole containing IRAK4 inhibitors designed to expand chemical diversity and improve off target activity of a previously identified series. These compounds maintain potent IRAK4 activity and desirable ligand efficiency. Rat clearance and a variety of off target activities were also examined, resulting in encouraging data with tractable SAR.